Globalisation and the Slope of the Phillips Curve - Emanuel Kohlscheen; Richhild Moessner (Center for Economic Studies and ifo Institute (CESifo), 2021)
We study the effects of globalisation on the slope of the New Keynesian Phillips curve for CPI inflation, based on a broad panel of 35 countries and controlling for possibly non-linear exchange rate effects. We find that the output gap generally has a significant positive effect on inflation, but that this effect decreases as integration in the global economy increases. We conclude that the advance of globalisation has been a key force behind the flattening of price Phillips curves across the world.
Keywords: E52; E58; 330; inflation; globalisation; openness; output gap; Phillips curve